FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA CABAI RAWIT DI KOTA MANADO - Nathania ., Palar; Paulus A., Pangemanan; Ellen G., Tangkere (Sam Ratulangi University, 2016)
This research aimed to analyze the factors affecting chili prices in the city of Manado, North Sulawesi. This is a quantitative research. The research was conducted in January 2016 to March 2016, data used are secondary data from the Department of Industry and Trade of the city of Manado, change price data from January 2015 until December 2015 and primary data from merchants of chili, curly chili, and tomato through questionnaire and interviews. Mechanical analysis is using multiple linear regression analysis. The result showed that demand of chili affects the price of chili.when public demand increases, the price also increasing vice versa. Also affect the price of a substitute when there is a decease or increase in the substitutes then chili also experienced the same thing, complementary goods prices also affect the price of chili. Tastes of public affect chili and prices for Manado City public taste inherently are spicy food lover so even if price are rising, buying chili is still substantial.*ls*